CFD analysis of the aerodynamic effects on the stability of the flight of a quadcopter UAV in the proximity of walls and ground. Issue 206 (November 2020) - Paz, C.; Suárez, E.; Gil, C.; Baker, C.
Abstract: Quadcopters are attracting a growing interest in many applications such as cargo delivery or surfaces inspection. These applications are often subjected to flights in the proximity of walls or ground that generate external forces and torques on the vehicle due to aerodynamic effects, because of what strong safety guarantees are required. In this research a methodology based on dynamic meshes was developed and applied to computational simulations to reproduce the flight of the drone over an obstacle. Thus, the effect of the ground proximity on the drone performance was assessed, and also its combination with the flow around the body at different translational velocities. The results shown a decrease of the drag force, and an increase of the lift and forward pitch moment due to the presence of the ground. These effects are magnified by the translational velocity, which also deviates the flow generated by the propellers and delays the interaction with the obstacle. Both in the approaching and leaving to the obstacle, increases of up to 60% in the pitch moment are observed. This sudden variations must be properly counteracted to guarantee the stability and safety of the drone operation. Highlights: The flight of a quadcopter over an obstacle was reproduced by CFD methodology. The effect of ground proximity was assessed for single rotor and quadrotor UAV. Ground effect reduces drag force and increases lift force and pitch moment. Significant flow oscillations are noted close to ground at low translational speeds. Strong changes of pitch moment are seen at the reaching and leaving of the obstacle.